Fe(III) phytate metallogel as a prototype anhydrous, intermediate temperature proton conductor - Aiyappa, Harshitha Barike; Saha, Subhadeep; Wadge, Pritish; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Science, 2015)
A proton conducting metallogel [FNPA; ferric nitrate (FN)-phytic acid (PA)] is synthesized by immobilizing a protogenic ligand (phytic acid) using iron(III) nitrate in DMF. The xerogel shows high proton conductivity of 2.4 x 10(-2) S cm(-1) at 120 degrees C, the best value known among all metal organic materials (MOMs). Marking the first such attempt in MOMs, an electrode made using the xerogel showed a power density of 0.94 mW cm(-2) at 0.6 V under dry fuel cell conditions.